Engineering nanoscale hypersonic phonon transport - Florez, O; Arregui, G; Albrechtsen, M; Ng, R. C; Gomis-Bresco, J; Stobbe, S; Sotomayor-Torres, C. M; García, P. D (Nature nanotechnology, 2022)
Controlling vibrations in solids is crucial to tailor their elastic properties and interaction with light. Thermal vibrations represent a source of noise and dephasing for many physical processes at the quantum level. One strategy to avoid these vibrations is to structure a solid such that it possesses a phononic stop band, that is, a frequency range over which there are no available elastic waves. Here we demonstrate the complete absence of thermal vibrations in a nanostructured silicon membrane at room temperature over a broad spectral window, with a 5.3-GHz-wide bandgap centred at 8.4 GHz. By constructing a line-defect waveguide, we directly measure gigahertz guided modes without any external excitation using Brillouin light scattering spectroscopy. Our experimental results show that the shamrock crystal geometry can be used as an efficient platform for phonon manipulation with possible applications in optomechanics and signal processing transduction.Nanopatterned materials provide control over mechanical vibrations. This allows for the complete damping of vibrations over more than 5 GHz and for the propagation of hypersonic guided modes at room temperature.